Pappa Ante Portas: The Retired Husband Syndrome in Japan - Marco Bertoni; Giorgio Brunello (Institute for the Study of Labor (IZA), 2014)
The "Retired Husband Syndrome", that affects the mental health of wives of retired men around the world, has been anecdotally documented but never formally investigated. We use Japanese micro data and the exogenous variation generated by the 2006 revision of the Japanese Elderly Employment Stabilization Law, which mandated employers to guarantee continuous employment between mandatory retirement age and full pension eligibility age, to estimate the causal effect of the husband's retirement on the wife's mental health. We find that adding one year to the time spent in retirement by Japanese husbands increases the probability that their wives develop the syndrome by 5.8 to 13.7 percentage points, depending on the empirical specification. We discuss mechanisms at work and argue that ceteris paribus increasing female labour force participation might exacerbate rather than attenuate the phenomenon.
Keywords: D1; I1; I3; J14; J26; 330; retirement; pension reforms; couples; stress; depression; Japan